Rituximab versus steroids and cyclophosphamide for the treatment of primary membranous nephropathy: protocol of a pilot randomised controlled trial. Issue 12 (4th December 2019) - Scolari, Francesco; Dallera, Nadia; Gesualdo, Loreto; Santoro, Domenico; Pani, Antonello; Santostefano, Marisa; Feriozzi, Sandro; Mani, Laila-Yasmin; Boscutti, Giuliano; Messa, Piergiorgio; Magistroni, Riccardo; Quaglia, Marco; et al.
Abstract : Introduction: Primary membranous nephropathy (MN) is a common cause of nephrotic syndrome in adults. The disease may have different long-term outcomes. After 10 years of follow-up, 35%–50% of the untreated patients with persistent nephrotic syndrome may die or progress to end stage renal disease. The 2012 KDIGO (Kidney Disease Improving Global Outcomes) guidelines recommend that initial therapy should consist of alternating steroids and an alkylating agent for 6 months. Recent observational studies showed that the anti-CD20 antibody rituximab may be effective in inducing remission. We designed a pilot multicentre randomised trial to inform the design of a larger trial testing the efficacy and safety of treatment with steroids and cyclophosphamide versus rituximab in patients with primary MN and heavy proteinuria (>3.5 g/24 hours). Methods and analysis: This pilot, open-label, two-parallel-arm, randomised clinical trial will enrol 70 patients with primary MN and heavy proteinuria. Patients will be randomised in a 1:1 ratio to either the intervention arm (rituximab) or the active comparator arm (corticosteroid/alkylating-agent therapy). The study will provide estimates of the probability of complete remission of proteinuria and risk of serious side effects at 12 months to inform the design of a larger trial. We will also assess the recruitment potential of each participating centre to address study feasibility. Ethics and dissemination: The trial received ethics approval from the local ethics boards. We will publish pilot data to inform the design of a larger clinical trial. Trial registration numbers: NCT03018535 ; 2011-006115-59.